Socio-Cultural Factors of the Russian Reforming Process of the 18-20th Centuries - Korobkov, Yuriy; Velikanova, Svetlana; Arakcheeva, Zinaida; Sannikova, Lilia; Levshina, Nataliya; Chernykh, Oksana (Journal of History Culture and Art Research, 2017)
The modern Russian reforms aimed at moving the society to a new stage of development are going through a complicated, contradictory way, with great social costs and zigzags of the political course of power. This poses the task of identifying and overcoming the inhibiting factors in the development of the country. One of the most effective mechanisms of such work is the study of the three-hundred-year experience of Russian reformation and the identification of timeless sociocultural and mental risk factors affecting the nature and content of reforms. This article is devoted to this purpose. In the course of study, we have drawn the conclusions about the deterrent effect on the development of the country of such features of Russian society as its socio-cultural split, absence of internal mechanisms for the self-development of society, lack of a dialogue between government and society, whose relationships are determined by the principle of "antisocial state - anti-state society", mental characteristics of the Russian intelligentsia, which dogmatically implements particular ideas at the expense of economic expediency and common sense, orientation of the ruling elite on the Western values as opposed to national traditions, conservatism and lack of conscious reformative motivation of the masses. This leads to the need to correlate the current reforms not only with the current trends of socio-economic development, but also with the sociocultural foundations of Russian society and the peculiarities of its mentality.